Hubungan Pengetahuan Dan Sikap Ibu Terhadap Capaian Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Sekip Palembang - Ike Sri Wahyuni, Adriani, Rizka Widya Astuti (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Exclusive breastfeeding (according to WHO) is feeding only breast milt to infants up to 6 mpnths old without other drinks or foods. Breast milk can be given until the baby is 2 years old. Exclusive breastfeeding can reduce mortality rate due to acute respiratory infections and diarrhea. This study ained to find out the relationship omong education and job towards the achievement of exclusive breastfeeding in the work area of Sekip Puskesmas. This study used analytical survey method with croos sectional approach. The population in this study was all mother having children aged 2 years old (182 respondents) visiting the Puskesmas and number of respondents was 65 taken using simple random sampling method. The results of the univariate analysis showed that 64.4 % respondents gave exclusive breastfeeding, 61.5% had good knowledge and 44.6% agreed.. This study used chi-square statistical test. The results of bivariate analysis showed that there was a significant relationship among had good knowledge and agreed toward the achievement of exclusive breastfeeding with p value of 0.007 and 0.008 respectivety. It is suggested to the Sekip Puskesmas to increase counseling about the importance of giving exclusive breastfeeding to infants aged 0-6 months as well as conducting counseling about the dangers that may occur to infants who are not exclusive breastfed and to reduce infant morbidity rate in Indonesia